1998
DOI: 10.1063/1.367277
|View full text |Cite
|
Sign up to set email alerts
|

Properties of amorphous and crystalline Ta2O5 thin films deposited on Si from a Ta(OC2H5)5 precursor

Abstract: In this work, the structural and electrical properties of amorphous and crystalline Ta2O5 thin films deposited on p-type Si substrates by low-pressure chemical vapor deposition from a Ta(OC2H5)5 precursor have been investigated. The as-deposited layers are amorphous, whereas crystalline Ta2O5 was obtained after postdeposition O2 treatment at 800 °C. As evidenced by x-ray diffraction, a hexagonal structure was obtained in the latter case. Physicochemical analysis of our layers shows that the O2-annealing step l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 28 publications
1
60
0
Order By: Relevance
“…Prior to application of sputter-deposited films it is necessary to understand the relation between microstructure, growth conditions, and resulting electrical and optical properties. A through optical study of such microstructure related effects was shown previously for magnetron sputtered boron nitride thin films [18][19][20][21] Tantalum oxide films ͑TOF͒ have been grown by a large variety of physical vapor deposition and chemical vapor deposition ͑CVD͒ processes, including ion beam sputtering, 22,23 magnetron sputtering, 2,7,9,24 ͑low temperature͒ thermal oxidation, 9,25 anodization, 26 ion plating, 1,27 electronbeam evaporation, 4,27 laser ablation, 28,29 low pressure CVD, 14,30 photo-CVD, 31,32 atomic layer deposition, 33 and plasma-enhanced CVD. 12,16,34 A metalorganic solution deposition technique 6 was also used to grow TOF.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Prior to application of sputter-deposited films it is necessary to understand the relation between microstructure, growth conditions, and resulting electrical and optical properties. A through optical study of such microstructure related effects was shown previously for magnetron sputtered boron nitride thin films [18][19][20][21] Tantalum oxide films ͑TOF͒ have been grown by a large variety of physical vapor deposition and chemical vapor deposition ͑CVD͒ processes, including ion beam sputtering, 22,23 magnetron sputtering, 2,7,9,24 ͑low temperature͒ thermal oxidation, 9,25 anodization, 26 ion plating, 1,27 electronbeam evaporation, 4,27 laser ablation, 28,29 low pressure CVD, 14,30 photo-CVD, 31,32 atomic layer deposition, 33 and plasma-enhanced CVD. 12,16,34 A metalorganic solution deposition technique 6 was also used to grow TOF.…”
Section: Introductionmentioning
confidence: 89%
“…3 Thin films of tantalum oxide are also employed as an ion conductor in electrochromic devices. 4,5 Known as a material with high static dielectric constant and with good electrical insulating properties, tantalum oxide has the potential for microelectronic applications as a capacitor and gate material, thereby replacing silicon dioxide in metal-insulator-metal [6][7][8][9][10][11] or metal-insulator-semiconductor [6][7][8][9][10][12][13][14][15][16][17] structures as well as in large-scale integrated circuits for dynamic random access memories. 6 Sputter-deposited thin films tend to show film porosity, which affects electrical or optical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leakage current-voltage characteristics have been explained in most cases by the Frenkel-Poole (FP) mechanism (bulk limited currents) [3][4][5][7][8][9][10][11][12][13] or by the Schottky emission of electrons from electrodes [2,7]. However, these models often faced difficulties when a quantitative comparison with experimental data was performed.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on the leakage current mechanism in thin films grown by various methods, with different electrode materials deposited on different substrates [2][3][4][5][6][7][8][9][10][11][12][13]. Leakage current-voltage characteristics have been explained in most cases by the Frenkel-Poole (FP) mechanism (bulk limited currents) [3][4][5][7][8][9][10][11][12][13] or by the Schottky emission of electrons from electrodes [2,7].…”
Section: Introductionmentioning
confidence: 99%